Geopolitical rivalry of global powers and its implications in Nepal - Wagle, Geja Sharma (Unity Journal, 2020)
National unity and independence, territorial integrity, people's sovereignty and national security are the supreme priority for any sovereign and independent country across the world. The essence of national unity and security is the most important and highly sensitive issue for Nepal in account of its geopolitical sensitivities and geostrategic balance as Nepal is located between two giant nuclear countries and rising global powers – India and China. Analyzing the national interests and national security policy of all three countries – India, China and the US, it is open secret that they have direct strategic, defense and security interests in Nepal. They, therefore, have strategic rivalry to extend their political, diplomatic, economic, strategic, defense and security and cultural influence in Nepal because of its geopolitical importance and geostrategic sensitivity. The emerging triangular strategic rivalry may undermine Nepal’s national interests and national security in the future as their rivalry gets intensified. It is a grave situation for Nepal which will have significant immediate as well as long-term implications. Nepal, therefore, should thoughtfully study to analyze the emerging global powers’ defense, military, security and foreign policies and strategies and should protect and preserve Nepal’s national interests and national security maintaining diplomatic and strategic balance among them.